Los alérgenos y su incidencia en el asma bronquial en niños menores de 7 años, comunidad San Lorenzo Cantón Vinces Los Ríos, periodo septiembre 2017 a febrero 2018 - Romero Bustamante, Andy Brian (2018)
The present investigation was carried out in the San Lorenzo del Cantón Vinces community through the use of the survey, the type of research that was used was Analytical: Because it consisted in the analysis and synthesis of cases of bronchial asthma. Descriptive: To analyze how is and how bronchial asthma manifests in relation to allergies. Projective: it is used to know how respiratory crises should be, to achieve some goals and improve lifestyle and it was looked for Identify the allergens that affect bronchial asthma in children under 7 years, analyze the impact of allergens in Asthma bronchial, investigate how the geographical area intervenes in the disease and propose a plan of action to raise awareness among parents about the consequences of bronchial asthma in children under 7 years, once this research was done, it was determined that they have Little knowledge about the causes that cause this health problem and mentioned that in the sector where they live do not have basic services, the same ones that would affect the development of allergens that cause asthmatic episodes in children under 7 years of age San Lorenzo of the canton of Vinces. And the proposal to design strategies to help reduce exposure to allergens that trigger bronchial asthma in children under 7 years, community San Lorenzo canton Vinces Los Ríos, period September 2017 to February 2018.